15 years on: Sam Harris’s Moral Landscape, a Retrospective Critique - Ragnar van der Merwe (Ethic@: an International Journal for Moral Philosophy, 2025)
In his best-selling book The Moral Landscape, Sam Harris develops a model for a universal ethics. His version of consequentialism has had some impact on the public, specifically on so-called new atheists. On the book’s 15th anniversary, I look back at and retrospectively critique Harris’s “science of morality” to see if it has stood the test of time. I first summarise the view, then identify various problems with it. Thereafter, I turn to arguably the most famous utilitarian, Peter Singer, for potential solutions to these problems. Since the publication of Harris’s book, Singer and Katarzyna de Lazari-Radek have written The Point of View of the Universe. This book looks to Henry Sidgwick’s The Methods of Ethics for answers to many of utilitarianism’s perennial challenges, some of which Harris does not ostensibly overcome. My aim is to investigate whether Singer and de LazariRadek’s utilitarianism (as informed by Sidgwick) can succeed where Harris’s version seemingly does not.